Understanding the Terms of the Building Approval Document for Small Commercial Buildings in Samarinda, following Government Regulations - Bakti, Yulya Puspita; Dinariyana, A.A.B. (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
As a substitute for the traditional Building Permit (IMB), the introduction of the Building Construction Permit (PBG) has engendered varying perspectives across numerous districts and cities throughout Indonesia. This incongruity is manifest in the PBG statistics spanning from August 2021 to March 2023, wherein, out of a total of 159,520 PBG applications, only 78,555, or 49.24%, were processed. Even when focusing specifically on East Kalimantan, among a total of 3,192 PBG applications, only 787, equivalent to 24.66%, received approval. In the provincial capital, Samarinda City, in May 2023, a mere 61 applications out of 1,058, constituting a mere 5.77%, obtained consent. The anticipated significant disparities to persist into early 2023 have raised concerns, particularly among small-scale entrepreneurs who seek an expeditious licensing process and are concerned about their well-being. Despite the implementation of an electronic or web-based system known as SIMBG, explicitly designed to streamline the PBG process, challenges endure. The main objective of this study is to explain the key aspects that need to be understood before proceeding with the PBG application procedure and fulfilling the document requirements in its preparation, drawn from insights found in existing literature. Furthermore, this study endeavors to facilitate public understanding and offer more directed solutions to enhance the prospects of success, spanning from the application phase to the issuance stage.